Nature and mystical beliefs in Biakolo’s Inotan and the River Goddess of and Sanusi’s La vie d’un enfant mystérieux - E S, Otegbale; Comfort Chioma, Olowolagba (South Asian Journal of Social Sciences and Humanities, 2025)
African literary works, since their inception with the advent of colonialism, have explored  diverse realities, ranging from critiques of colonial legacies to dictatorship, women's  subjugation and empowerment, civil unrest on the African continent, migration, as well as the  importance of nature in human day-to-day living. Environmental discourse in African  literature, expressed in both English and French, has primarily focused on the aesthetics of  nature and human nefarious activities that pose a danger to both nature and human existence,  with little attention given to spirituality and mysticism. Using the comparative model as a  method and magical realism as a framework, this research seeks to demonstrate that  indigenous mystical beliefs are intricately tied to the natural environment. Specifically, water  bodies (rivers) and trees are identified as key mystical habitats while shedding light on the  multifaceted nature of African mystical beliefs and their profound connection to the  environment. The research argues that nature transcends mere aesthetics, serving as a  complex and enigmatic realm accessible only to those initiated into its ontological  landscapes, as it reveals a deeper understanding of the intricate relationship between culture,  spirituality, and the environment in African literature. It also highlights the significance of  acknowledging the diversity of mystical beliefs shaped by distinct ecological landscapes,  with potential implications for environmental discourse.
Keywords: Nature; Mystical beliefs; Environment; Cosmology; Nigeria